Tax oversight for ensuring compliance and enhancing the investment climate - Atmani, Karima (The International tax journal, 2025)
The establishment of tax oversight has led to the adoption of a set of substantive and procedural controls. This is clearly reflected in the Tax Procedures Code, which serves as the legal framework for all forms of tax audits and investigations. This regulatory structure aims to promote transparency and ensure tax compliance, thereby contributing directly to the creation of a sound investment environment. The legislator has emphasized declaration oversight as a primary form of control, and tax investigations as an in-depth mechanism, both of which help strengthen business stability and foster investment.